2018
DOI: 10.2134/agronj2017.09.0547
|View full text |Cite
|
Sign up to set email alerts
|

Maize Yield Response to Nitrogen Rate and Plant Density under Film Mulching

Abstract: However, irrational N application regimes (Liu et al., 2014b; Li et al., 2015) and low plant densities (Liu et al., 2014a) are the key factors limiting the further improvement of crop yield and resource use efficiency in this mulching system. N fertilizer plays a significant role in improving grain yield and WUE (Hernández et al., 2015; Li et al., 2015). Previous research focusing on contrasts in water availability (i.e., rain-fed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The application of slow released fertilizer has been proven to increase the grain yield and NUE of maize compared with conventional urea by numerous studies (Diez et al, 1994;Hu et al, 2013;Zhao et al, 2013;Zheng et al, 2016Zheng et al, , 2017. Increased plant population density could increase grain number and decrease grain weight in maize production (Li et al, 2018;Poneleit & Egli, 1979;Rossini, Maddonni, & Otegui, 2011), and N starvation exerted negative effects on final kernel numbers and weight (Boomsma, Santini, Tollenaar, & Vyn, 2009;Hokmalipour et al, 2010;Li et al, 2018). Our results indicated that SF application was better than CF in increasing F I G U R E 7 Relationships between nitrogen accumulation at maturity, pre-silking N, post-silking N, specific leaf N and grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…The application of slow released fertilizer has been proven to increase the grain yield and NUE of maize compared with conventional urea by numerous studies (Diez et al, 1994;Hu et al, 2013;Zhao et al, 2013;Zheng et al, 2016Zheng et al, , 2017. Increased plant population density could increase grain number and decrease grain weight in maize production (Li et al, 2018;Poneleit & Egli, 1979;Rossini, Maddonni, & Otegui, 2011), and N starvation exerted negative effects on final kernel numbers and weight (Boomsma, Santini, Tollenaar, & Vyn, 2009;Hokmalipour et al, 2010;Li et al, 2018). Our results indicated that SF application was better than CF in increasing F I G U R E 7 Relationships between nitrogen accumulation at maturity, pre-silking N, post-silking N, specific leaf N and grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of roots in supporting intensive cropping systems in which plant density is high and fertilizers are largely available has been considerably less heavily studied and discussed (Mi, Chen, Yuan, & Zhang, 2016). As the soil hydrothermal conditions, WUE and maize yield were significantly improved under FM (Li et al., 2018; Liu, Li, Chen, Yang, & Chen, 2010a, 2010b, 2014), and the biomass allocation in roots and shoots should also be different. Some researchers found that FM had significant effects on the development of maize roots (Gao, Xie, Jiang, Wu, & Niu, 2014; Wang et al., 2018; Xiao et al., 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…In semi-arid areas, N fertilization was shown to increase crop production under dry conditions with poor water supply [10,11]. However, crop yield may be decreased with the excessive application of N fertilizer [12]. In addition, N fertilizer applied more than crop need can lead to nitrate accumulation in the soil profile and degrade both surface and groundwater resources, resulting in eutrophication and non-potable water supplies [13,14].…”
Section: Introductionmentioning
confidence: 99%